Perancangan Pembangkit Listrik Hybrid dengan Tenaga Surya dan Tenaga Mikrohidro - Yulanda, Erik Agustian; Susilo, Joko Tri; Tama, Agi; Sunardi, Sunardi; Prakoso, Dony Agus; Yanuar, Ahmad (Universitas Pamulang, Prodi teknik Elektro, 2024)
Efforts to provide electrical energy in remote areas are by utilizing available natural potential such as solar radiation and water flow rates, so that designing a hybrid power plant based on solar power and micro hydro becomes appropriate. This research aims to design an optimal hybrid power generation system by utilizing each energy source. The design method includes analysis of potential solar radiation and river water flow, selection of main components and system design. The measurement results over a period of seven days show an average light intensity of 5106 lux and an average water discharge of 1.24 m3/s. Based on system test results, the PLTS power is 110.27 Watts and the PLTMH power is 170.09 Watts, so the total energy is 280.36 Watts (0.280 kW). In conclusion, the application of hybrid power plants with solar power and micro hydro power in remote areas has great potential.